Knowledge Level of Smallholder Woman Farmers of Poultry Producer Company in Madhya Pradesh - Raj Kumar Patel,; Mahesh Chander,; Med Ram Verma, R. Hari, (Indian Journal of Extension Education, 2022)
The poultry producer companies provide trainings and extension services to their members. The present study was conducted in 2021-22 in Madhya Pradesh state to assess the impact of poultry Producer Company on knowledge level of smallholder women poultry farmers of company. Ex-post facto research design was used. Multistage sampling was done for the selection of respondents. Data was collected from randomly selected, 140 members and 140 non-members, through a structured interview schedule. Propensity score matching was applied at 0.2 tolerance level, to reduce extraneous variable effect and finally 96 members and 96 non-members respondents were selected for data analysis and interpretation of results. The majority of the members had medium to a high level of knowledge of poultry housing, brooding, litter management and feeding while medium to low level of knowledge of healthcare management, whereas, most non-members had a medium to low level of knowledge of poultry housing, litter management, feeding, and healthcare, and medium to high level of knowledge of brooding. There was a significant difference in knowledge of members and non-members at 0.1% level of significance regarding housing, litter management, and feeding and interpreted as poultry producer company had positive impact on knowledge of member poultry farmers